Aktualne możliwości i perspektywy wykorzystania fungicydów w leśnictwie - Okorski, Adam; Nowakowska, Justyna; Oszako, Tomasz; Pszczółkowska, Agnieszka (Leśne Prace Badawcze, 2026)
The possibility of using chemicals in European forestry is extremely limited due to the binding legal regulations and specific conditions concerning the market of plant protection products. This is reflected in the limited availability of active fungicides in forestry. Due to this limitation, practitioners using fungicides in forest nurseries and forest cultivation must have substantial knowledge of the biology of pathogens to ensure satisfactorily effective protection. The work presented here provides an overview of the currently recommended fungicides in Polish forestry as well as the mechanisms of interaction between the active substances and the pathogen, the plant and mycorrhizal fungi. In this paper we also discuss the risk of fungicide resistance, which has been insufficiently explored in the context of forest pathogens.